No longer restricted to Asia: the exotic snail Solenomphala scalaris (Caenogastropoda: Assimineidae) is widespread in Brazil - Maurício R. Fernandes; Igor C. Miyahira; Isabela C.B. Gonçalves; Sonia B. dos Santos; Fabiano Salgueiro; Jucicleide Ramos-de-Souza; Suzete R. Gomes (Zoologia (Curitiba))
ABSTRACT The assimineid Solenomphala scalaris (Heude, 1882) is present in the interface between freshwater and terrestrial habitats. It was originally described from China, but it has been recently recorded it from Singapore and Malaysia, in addition to possible records from Taiwan, Japan and Elba, Italy. Sampling efforts in four Brazilian states (Amazonas, Rio de Janeiro, São Paulo and Santa Catarina) since 2009 recovered specimens similar to S. scalaris, always in anthropic sites. The shell, operculum, radula and penis largely agree with descriptions and images of S. scalaris available in the literature. The mitochondrial gene COI was sequenced for 25 specimens from Brazil, revealing that two genetic lineages (diverged by 1.9-2.5%) are widespread in that country, one of which is also present in China and Taiwan. Additional sampling in native and non-native sites is required to test whether S. scalaris is synonymous with other species from East Asia. Solenomphala scalaris is a cryptic exotic species; due to its minute shell and simple morphology, S. scalaris has most likely gone unnoticed in its introduced range.